THE IMPORTANCE OF INNOVATIVE MOBILE APPLICATIONS IN CONTROLLING CONSTRUCTION PROCESSES (Multidisciplinary Journal of Science and Technology, 2026)
This article explores the role and significance of innovative mobile applications in controlling construction processes. By analyzing the limitations of traditional methods, the article examines the advantages of mobile technologies in real-time monitoring, data collection, ensuring safety, and increasing efficiency. Furthermore, it discusses the transformative impact of mobile applications on the construction industry through examples of integrating modern technologies such as IoT, AI, and AR. Consequently, the potential of mobile applications in optimizing construction projects, reducing costs, and ensuring environmental sustainability is highlighted, while suggestions for future development trends are provided.